Effects of Motherwort Injection Versus Intramuscular Oxytocin for Preventing Postpartum Hemorrhage Among Women Who Underwent Cesarean Section - Li, Ming-xi; Liu, Chun-rong; Chen, Meng; Shang, Hong-cai; Wang, Wen; Luo, Xiao-chao; Li, Ling; Qi, Ya-na; Xiong, Yi-quan; Huang, Shi-yao; Wang, Jing; Zou, Kang; et al. (Frontiers in Pharmacology, 2022)
Objectives: Subject to ethical constraints, real-world data are an important resource for evaluating treatment effects of medication use during pregnancy and postpartum period. This study investigated whether motherwort injection, a traditional Chinese medicine preparation, was more effective than intramuscular (IM) oxytocin for preventing postpartum hemorrhage (PPH) in a real-world setting, when intravenous (IV) oxytocin is administered. Methods: We conducted an active-controlled, propensity-score matched cohort study using an established pregnancy registry database. Women who underwent cesarean section and all received IV oxytocin at the third stage of labor were included. We used an active-comparator design to minimize indication bias, in which we compared IM motherwort injection in the uterus versus IM oxytocin, both on top of IV oxytocin use. We applied 1:1 propensity-score matching (PSM) to balance patient baseline characteristics, and used logistic regression model to estimate treatment effect (i.e., risk difference (RD) and odds ratio (OR)) by using the counterfactual framework. The outcomes of interest were blood loss over 500 mL within two hours after delivery (PPH, primary) and blood loss over 1,000 mL (severe PPH, secondary). We conducted four sensitivity analyses to examine the robustness of results. Results: A total of 22,519 pregnant women underwent cesarean sections, among which 4,081 (18.12%) PPH and 480 (2.13%) severe PPH occurred. Among included women, 586 (2.60%) were administrated with IM motherwort injection, and 21,933 (97.40%) used IM oxytocin. After PSM, patient baseline characteristics were well balanced. Compared with IM oxytocin, the use of IM motherwort injection was associated with significantly lower risk of PPH (RD -25.26%, 95%CI -30.04% to -20.47%, p<0.001; OR 0.25, 95%CI 0.18 to 0.32, p<0.001) and severe PPH (RD -3.58%, 95%CI -5.87% to -1.30%, p<0.001; OR 0.39, 95%CI 0.20 to 0.71, p<0.002). Sensitivity analyses showed the results were similar. Conclusion: Using data from real-world setting, the findings consistently showed that among women undergoing cesarean section who had received IV oxytocin, the additional use of IM motherwort injection could achieve lower risk of PPH compared to the additional use of IM oxytocin. Our study suggested a paradigm for investigating treatment effect of Chinese herbal medicine in the real-world practice setting.